A taxonomic revision of Palaearctic Chionodes (Lepidoptera: Gelechiidae). - Huemer, Peter; Sattler, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1995)
The Palaearctic species of the genus Chionodes Hübner, [1825], are revised; 28 species are recognized as valid; 6 species are newly described; 8 new synonyms and one new combination are established and lectotypes are designated for 26 nominal species. Separate keys to the males and females are provided, based on genitalia and wing characters. Data on the biology of the species are summarized. The adults and the male and female genitalia are illustrated. Nomenclatural Acts aprilella Huemer & Sattler, 1995 (Chionodes), spec. n. carpella Psikunov, 1971 (Chionodes), syn. n. of Chionodes fumatella (Douglas, 1850) caucasicella Huemer & Sattler, 1995 (Chionodes), spec. n. continuella (Zeller, 1839) (Chionodes), Lectotype described as Gelechia continuella deserticola Piskunov, 1979 (Chionodes), syn. n. of Chionodes distinctella (Zeller, 1839) distinctella (Zeller, 1839) (Chionodes), Lectotype described as Gelechia distinctella electella (Zeller, 1839) (Chionodes), Lectotype described as Gelechia (Gelechia) electella flavipalpella Huemer & Sattler, 1995 (Chionodes), spec. n. frigidella Huemer & Sattler, 1995 (Chionodes), spec. n. fumatella (Douglas, 1850) (Chionodes), Lectotype described as Gelechia fumatella ignorantella (Herrich-Schäffer, 1854) (Chionodes), Lectotype described as Gelechia ignorantella lugubrella (Fabricius, 1794) (Chionodes), Lectotype described as Tinea lugubrella nubilella (Zetterstedt, 1839) (Chionodes), Lectotype described as Haemylis nubilella sagayica (Koçak, 1986) (Chionodes), comb. n. described as Gelechia sagayica soella Huemer & Sattler, 1995 (Chionodes), spec. n. tannuolella (Rebel, 1917) (Chionodes), Lectotype described as Gelechia tannuolella tantella Huemer & Sattler, 1995 (Chionodes), spec. n. ukrainica Piskunov, 1979 (Chionodes), syn. n. of Chionodes mongolica Piskunov, 1979 viduella (Fabricius, 1794) (Chionodes), Lectotype described as Tinea viduella violacella (Tengström, 1848) (Chionodes), Lectotype described as Gelechia violacella celerella Stainton, 1851 (Gelechia), Lectotype now a synonym of Chionodes fumatella (Douglas, 1850) cognatella Heinemann, 1870 (Gelechia), Lectotype now a synonym of Chionodes holosericella (Herrich-Schäffer, 1854) danieli Osthelder, 1951 (Gelechia), Lectotype now a synonym of Chionodes holosericella (Herrich-Schäffer, 1854) libidinosa Staudinger, 1871 (Gelechia), Lectotype now a synonym of Chionodes tragicella (Heyden, 1865) nigricans Heinemann, 1870 (Gelechia), Lectotype now a synonym of Chionodes fumatella (Douglas, 1850) ochripalpella Frey, 1880 (Gelechia), Lectotype now a synonym of of Chionodes hayreddini Koçak, 1986 oppletella Herrich-Schäffer, 1854 (Gelechia), Lectotype now a synonym of Chionodes fumatella (Douglas, 1850) sauteriella Zeller, 1868 (Gelechia), Lectotype now a synonym of Chionodes luctuella (Hübner, 1793) tarandella Wocke, 1864 (Gelechia), Lectotype now a synonym of Chionodes nubilella (Zetterstedt, 1839) latiorella Amsel, 1939 (Gelechia distinctella), Lectotype; syn. n. of Chionodes distinctella (Zeller, 1839) unicolor Toll, 1948 (Gelechia distinctella), Lectotype; syn. n. of Chionodes distinctella (Zeller, 1839) indistinctella Rebel, 1901 (Gelechia distinctella var.), Lectotype; syn. n. of Chionodes distinctella (Zeller, 1839) brunnea Teich, 1901 (Gelechia nigricans var.), syn. n. of Chionodes fumatella (Douglas, 1850) meesi Barca, 1932 (Gerlechia norvegiae var.), Lectotype; syn. n. of Chionodes holosericella (Herrich-Schäffer, 1854) lunatella Zetterstedt, 1839 (Lita), Lectotype now a synonym of Chionodes lugubrella (Fabricius, 1794)